2021
DOI: 10.1016/j.celrep.2021.109125
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput genome-wide RNAi screen identifies modifiers of survival motor neuron protein

Abstract: Spinal muscular atrophy (SMA) is a debilitating neurological disorder marked by degeneration of spinal motor neurons and muscle atrophy. SMA results from mutations in survival motor neuron 1 (SMN1), leading to deficiency of survival motor neuron (SMN) protein. Current therapies increase SMN protein and improve patient survival but have variable improvements in motor function, making it necessary to identify complementary strategies to further improve disease outcomes. Here, we perform a genome-wide RNAi screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The THOC3 gene, located on chromosome 5, encodes a protein that is a highly conserved part of the TREX complex. THOC3 plays a crucial regulatory role in splicing and recruitment during transcription, and it is also an important factor in regulating RNA-binding proteins (RBPs), as con rmed by existing research [22,39,40] . Currently, research on THOC3 in cancer is limited to a few speci c types of cancer, such as lung squamous cell carcinoma and glioma, with no studies yet addressing THOC3 in various cancer types.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The THOC3 gene, located on chromosome 5, encodes a protein that is a highly conserved part of the TREX complex. THOC3 plays a crucial regulatory role in splicing and recruitment during transcription, and it is also an important factor in regulating RNA-binding proteins (RBPs), as con rmed by existing research [22,39,40] . Currently, research on THOC3 in cancer is limited to a few speci c types of cancer, such as lung squamous cell carcinoma and glioma, with no studies yet addressing THOC3 in various cancer types.…”
Section: Discussionmentioning
confidence: 85%
“…Aberrant expression of the THO complex may lead to imbalance in intracellular information transmission, affecting normal cell growth and death processes. Recent research has progressively uncovered THOC3's role in cancer development , McCormack NM and colleagues demonstrated that silencing the THOC3 gene markedly increases SMN protein levels, which regulate RNA metabolism and are closely linked to cell migration, invasion, and adhesion [22,23] . Yu T and colleagues discovered that elevated THOC3 expression leads to an increase in PFKFB4 levels, which consequently enhances glycolysis and facilitates the progression and motility of LUSC cells [24] .…”
Section: 0: Introductionmentioning
confidence: 99%
“…Given the strong importance of mitochondria in all cell types, and especially in MNs and muscles, we are convinced that future studies should focus on the identification of new mitochondrial-related modifiers of SMA pathology. Genetic screenings for new modifiers recently conducted both in D. melanogaster [199] and human HEK cells [200] highlighted new potential mitochondrial candidates (Table 1).…”
Section: Mitochondrial Functions: Potential Sma Modifiers?mentioning
confidence: 99%